Gastropod Diversity in the Pandayangan River, South Labuhanbatu Regency - Alex Parmonangan Tobing; Arman Harahap (Budapest International Research and Critics University, 2021)
This study aims to determine the diversity of Gastropods in the Pandayangan River, South Labuhanbatu Regency. Descriptive exploratory research was conducted at 3 stations from December to February 2021. Gastropod samples were taken from the sampling results at the time of the study in the Pandayangan River. Samples were taken from 3 stations with different characteristics, the gastropods were washed and documented. The identification process is carried out using the identification key of the Jutting book. The results obtained 7 types of Gastropods from 3 families of Thiaridae, Ampullariidae and Viviparidae, namely Brotia castula, Melanoides tuberculata, Melanoides punctate, Pomacea canaliculata, Pila polita, Pila ampullacea and Filopaludina sumatrensis. Gastropods catch 230 individuals. Station I found 40 individuals, Station II was found 80 individuals and Station III was found 110 individuals. Types of Brotia castula, Melanoides punctate, and Pomacea canaliculata were mostly found at Station II and Station III.